(untitled) (ModaPalavra e-periódico, 2020)
The article emphasizes the development of the ability to articulate visual / formal syntax as a fundamental way for the consolidation of project thinking among fashion design students. From exploratory approach, integrates two research focus: the first stu dies the self - regulation of learning in project teaching; the second one addresses methodological strategies for the development of the ability compositional synthesis. Thus, the study examines practices for Visual Methodology learning at the Bachelor of t he Fashion Design at State University of Londrina, searching effective contributions the experimental creative manipulation and decomposition of visual messages. To that occurs, a combined pedagogical action is analyzed, aiming at the proof of its didactic scholarship. The results confirm the potential of action and self - regulated learning strategies as facilitators of the ability to generate expressive and configurable concepts of artifacts in the field of fashion